Resistant legacies - Pavoni, A. (2015)
This paper addresses the dialectic between mega events (MEs) and the city, and especially the frictions generated by their encounter, which the current wave of protest and resistance to MEs provides with both a significant expression as well as a locus for conceptual and empirical exploration. First, I introduce the argument by looking at the spatiality of neoliberal capitalism through the abstract form of the urban it presupposes and the concrete affective, material and atmospheric assemblages through which it is actualized in the contemporary city – a process, I argue, which is always problematized by frictions, conflicts and contradictions. Second, I situate this discussion vis-à-vis what Jacob (2013) terms the eventification of urban space and particularly the peculiar contradiction it expresses: namely, that urban space increasingly becomes the locus of both the production and prevention of events – a contradiction whose effects can be most cogently observed in the current erosion of the right to protest in the contemporary city. Third, I introduce the ME as the site in which this dialectic and its contradictions are most forcefully expressed. MEs are the quintessential urban event, at the same time an intense generation of urban ‘effervescence’ (Durkheim, Emile. 2008. The Elementary Forms of Religious Life. Oxford University Press), and an apparatus aimed at channelling such effervescence into safe and capitalizable expressions. However, this process of ‘controlled decontrolling’ [Elias and Dunning. 1971. ‘Leisure in the Sparetime Spectrum’. In Sociology of Sport, edited by R. Albonic and K. Pfister-Binz. Birkhäuser] is always disjointed by the urban contingency in which it takes place, unintentionally producing frictions that are fraught with political potential. If the notion of legacy, as I suggest, is what cements the late interspersion between MEs and capitalist urbanization, then deconstructing legacy could provide a fresh perspective to explore the relation among MEs, urban space and resistance. Therefore, fourth, I introduce the concept of ‘resistant legacies’, whereby I propose to address conceptually and empirically the frictions produced by MEs and the impact and legacy they may leave on the social, affective and normative fabric of the city, by suggesting the current wave of ME protests as a promising site for this exploration. Finally, I conclude with some methodological suggestions for future research.